Differential methods of localisation of fungal endophytes in the seagrasses. Issue 3 (2nd July 2016) - Raja, S.; Subhashini, Pon.; Thangaradjou, T.
ABSTRACT: Sections of three seagrass species ( Halophila ovalis, Cymodocea serrulata and Halodule pinifolia ) were assessed for endophytes based on differential staining using light and fluorescence microscopy method. Acridine orange and aniline blue detected endophytic fungi in 20% and 10% of the segments, respectively, whereas lactophenol cotton blue was more sensitive to detect the fungal hyphae in 70% of the segments. Hyphae were the principal fungal structures generally observed under the cuticle, within the epidermal cells, mesophyll (Parenchyma) cells and occasionally within the vascular tissue that varied in type, size and location within the leaf tissue. Present study also recorded the sporulation for the first time from the seagrass endophytes. Successfully amplified products of the ITS region of endophytic fungal DNA, directly from seagrass tissue and also from culture-dependent fungal DNA clearly depicted the presence of endophytic fungi in H. ovalis with two banding patterns (903 and 1381 bp) confirming the presence of two dominant fungal genera. The fingerprinting of endophytic fungal community within the seagrass tissue was assessed using denaturing gradient gel electrophoresis (DGGE) that derived with multiple bands that clarified the presence of more than one taxon within the seagrass tissue.